Oxidation Characteristics of Functional Groups in Relation to Coal Spontaneous Combustion - Zhang, Yutao (ACS Omega, 2021)
[Image: see text] To investigate and better understand the mechanism of coal spontaneous combustion, the distributions, evolution, and oxidation characteristics of functional groups in different coal samples were characterized using in situ Fourier transform infrared (FTIR) and electron paramagnetic resonance (EPR) experiments. The macroscopic characteristics of coal spontaneous combustion in relation to functional groups were also analyzed using the thermogravimetric/differential scanning calorimetry–FTIR coupling technique. The experimental results indicated that −OH was the most active groups of coal spontaneous combustion. It not only could react with the absorbed oxygen spontaneously but also found to be the main product of the chemisorption. Consequently, −OH was believed to contribute most both for the loss and increase of coal mass during the process of spontaneous combustion. Aliphatic hydrocarbons were the main components to form −C–O–O(•) and could be further oxidized into C=O. However, reactions between aliphatic hydrocarbons and oxygen were nonspontaneous. EPR experiments suggested that the tendency of coal spontaneous combustion acutely depended on the stability and survival time of free radicals. The more the stable and longer survival time of free radicals are, the lower the tendency of coal spontaneous combustion is.